Development of an Engineered Photoactive Yellow Protein as a Cross‐Linking Junction for Construction of Photoresponsive Protein‐Polymer Conjugates. Issue 6 (16th April 2019) - Ui, Mihoko; Miyauchi, Yusuke; Inoue, Masataka; Murakami, Makoto; Araki, Yasuyuki; Wada, Takehiko; Kinbara, Kazushi
Abstract: Based on a bacterial blue light photoreceptor, photoactive yellow protein (PYP), we have developed a photoresponsive protein module, Hpg5‐PYP, bearing five alkynyl groups as reactive sites. We constructed a yellow‐colored photoresponsive protein–polymer conjugate by using covalently bonded Hpg5‐PYP with poly( N, N ‐dimethylacrylamide‐co‐2‐hydroxy‐3‐azidopropyl methacrylate) (DMA‐HAZPMA copolymer). Hpg5‐PYP retained photoreactivity towards blue‐light irradiation in the conjugate, and the conjugate showed a photoresponsive viscosity change upon irradiation with blue light at 25 °C. In contrast, a mixture of Hpg5‐PYP and DMA‐HAZPMA copolymer prepared for reference did not show any dependency of the viscosity on light irradiation, indicating the importance of crosslinking. Abstract : It was all yellow : Based on a bacterial blue light photoreceptor, photoactive yellow protein (PYP), we have developed a photoresponsive protein module, Hpg5‐PYP, bearing five alkynyl groups as reactive sites and used it to construct a yellow‐colored photoresponsive protein–polymer conjugate. The conjugate showed a photoresponsive viscosity change upon blue‐light irradiation at 25 °C.